2023
DOI: 10.3389/fpsyg.2023.1031294
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the digital economy on enterprise innovation behavior: Based on CiteSpace knowledge graph analysis

Abstract: IntroductionAs a new trend, the digital economy will promote “digital industrialization” in the process of promoting “industrial digitalization.” It can accelerate technological innovation by adjusting managerial behavior and strategic decisions, promoting and protecting technological research and development, and providing technological infrastructure. While technological innovation, which generally occurs in enterprises, will promote a new round of upgrading, optimization, and even reshaping of the whole ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Technological innovation caused indirect positive influence of the digital economy is found on the speed of industrial restructuring and industrial structure supererogation and rationalization. These findings are consistent with the findings of existing studies [16,45,47,51].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Technological innovation caused indirect positive influence of the digital economy is found on the speed of industrial restructuring and industrial structure supererogation and rationalization. These findings are consistent with the findings of existing studies [16,45,47,51].…”
Section: Discussionsupporting
confidence: 93%
“…The analysis of property rights theory and transaction cost theory from new institutional economics; and the research on changes in innovation subjects, technologies, and behavioral approaches from innovation theory [3]. Yu et al (2023) found that the research on enterprise innovation behavior in the digital economy era has formed eight research directions, such as expertise, human capital FSA, integration in global value chains, financial innovation, fintech, people preference shift, internet of everything, and consumer co-creation [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The digital economy has profoundly impacted innovation [52]. First, the digital economy provides essential infrastructure and accelerates technological innovation [53]. Knowledge and talent have an essential impact on innovation activities [54].…”
Section: Plos Onementioning
confidence: 99%